Critical Citation in a Canadian Context: The Development of Citation Justice Resources at the University of Victoria Libraries - Mussell, Jessica; Lampreau, Jessie; Dean, Heather (KULA)

(untitled) (University of Victoria Libraries, 2026)
This project report provides an overview of a citation justice project developed at the University of Victoria Libraries, a Canadian academic library, as part of a broader library initiative aiming to address inherent biases within traditional scholarly publishing and academic research practices. Leveraging the unique position of libraries and information specialists as partners in the research process, this report details the steps undertaken, lessons learned, and future plans for advancing critical citation and inclusivity in academic scholarship.